Unveiling of bio-inspired synthesis, characterization, DFT calculations, molecular modeling of silver (Ag/Ag2O) nanocomposite: A promising sustainable material against human breast cancer - R. Kavitha; M. Srinivas; Prashantha Karunakar; G.R. Rekhashree; R. Priyanka; K.G. Shilpashree; M.S. Kavya; S.M. Basavarajaiah (Tetrahedron Green Chem)
The extensive use of nanocomposites in the field of medicine and pharmaceuticals stems from their physicochemical properties and due to their potential therapeutic application. Further, nanopharmaceutics take a significant role in designing smart drug-release and controlled drug delivery, where the drug is efficiently reached towards the target sites within a predictable and limited timescale. The scope of present research work is to synthesis an ecofriendly silver nanocomposite (Ag/Ag2O) by using alcoholic fruit extract of Pheonix slyvestris and its efficiency was evaluated for anticancer activity. PXRD results and HRTEM images confirmed that Ag/Ag2O was crystalline in nature with diverse morphology and possessed an average particle size of 23–50 nm. Surface plasmon resonance of Ag/Ag2O was observed at 465–500 nm in UV-DRS. The PL spectrum of Ag/Ag2O NPs shows two asymmetric peaks confirming the formation of Ag/Ag2O heterocomposite. The cytotoxicity study Ag/Ag2Osynthesized via green chemistry was performed using the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyltetrazolium bromide) assay against breast cancer cell line (MCF7) with an IC5021.61 μg/mL. The results of the cytotoxicity tests showed a concentration dependent outcome against tumor cells and a correlation between dosage and effectiveness against tested cancer cell line. DFT studies revealed the sensing response of Ag/Ag2O composite towards doxorubicin drug confirmed by relative work function changes. Molecular docking and dynamics simulation resulted that the Ag/Ag2O illustrates to be an excellent lead molecule. In conclusion, the present research work demonstrated that Ag/Ag2O synthesized from alcoholic fruit extract of Pheonix slyvestris may be an impending remedial drug for breast cancer management.